HUBUNGAN ANTARA KADAR 8HYDROXY2DEOXYGUANOSINE SERUM DENGAN FUNGSI KOGNITIF PADA STROKE ISKEMIK - Alya Tursina , Andi Basuki Prima Birawa, Dede Gunawan, Anna Tjandrawati (NEURONA, 2015)
INTRODUCTION POSTSTROKE DISABILITIES ATTRIBUTED TO PHYSICAL DISORDERS CAN BE WORSENED BY THE PRESENCE OF COGNITIVE DYSFUNCTION SERUM 8HYDROXY2DEOXYGUANOSINE 8OHDG IS THE RESULT OF FREE RADICAL INTERACTION WITH THE C8 GROUP OF GUANINE BASE INCREASED SERUM 8OHDG CONCENTRATION INDICATES NEURONAL DAMAGE AND AFFECTS COGNITIVE FUNCTION IN ISCHEMIC STROKE PATIENTS EXAMINED USING MONTREAL COGNITIVE ASSESSMENTINDONESIA VERSION MOCAINA